Miss Peregrine's journal for peculiar children featuring vintage photographs and excerpts from the Peculiar Children series by Ransom Riggs - Riggs, Ransom (Quirk Books, 2016)
Guided journal based on the New York Times #1 Bestseller Miss Peregrine's Home For Peculiar Children- the basis for the soon to be released Tim Burton film